2019
DOI: 10.1109/access.2019.2924181
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Sleep Bruxism Using Power Spectral Density Approach Applied on EEG Signal of Both EMG1-EMG2 and ECG1-ECG2 Channels

Abstract: Bruxism is a sleep syndrome, in which individual involuntarily grinding and clenching the teeth. If sleep does not complete properly, then it generates many disorders such as bruxism, insomnia, sleep apnea, narcolepsy, rapid eye movement behavioral disorder, and nocturnal frontal lobe epilepsy. The aim of this paper is to draw the results in the form of signal spectrum analysis of the changes in the domain of different stages of sleep. The present research completed in three stages such as the collection of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 38 publications
1
47
0
Order By: Relevance
“…Previously, we designed the diagnostic of bruxism sleep syndrome and sleep stages using a decision tree classifier with 81.25% accuracy [19]. Lai et al [40] showed that the ECG channel and EMG channel are used for the detection of bruxism syndrome using power spectral density (PSD) techniques. They used the 488-min data for the two channels and classification of the subjects and stages using the machine learning method.…”
Section: Classification Results Using Proposed Novel Hml Classifiermentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we designed the diagnostic of bruxism sleep syndrome and sleep stages using a decision tree classifier with 81.25% accuracy [19]. Lai et al [40] showed that the ECG channel and EMG channel are used for the detection of bruxism syndrome using power spectral density (PSD) techniques. They used the 488-min data for the two channels and classification of the subjects and stages using the machine learning method.…”
Section: Classification Results Using Proposed Novel Hml Classifiermentioning
confidence: 99%
“…The physiological sleep channels, including ECG1-ECG2, EMG1-EMG2, C4-P4, and C4-A1 of the bruxism and healthy subjects, are shown in Figures 3 and 4 [19,40,48]. The 10/20 standard sleep recording system records these channels.…”
Section: Analysis Of the Physiological Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data is typically acquired directly from the human component of the system via the EEG headset, which is analysed with various possible techniques contingent on the psychological information required. Spectral analysis is one of the standard methods used to quantify EEG data, where the Power Spectral Density (PSD) component reflects the distribution of signal power over frequency [28], which is employed for a variety of applications in medicine [29], [30]. In many of these measurement-based systems the subject does not actively, explicitly, or voluntarily modulate EEG activity, instead focussing on the task [31]; this popular configuration is known as pBCI.…”
Section: Related Work a Eeg In Human-machine Systemsmentioning
confidence: 99%
“…Lai et al used the physionet database for the prognosis of bruxism. Their proposed scheme gives high detection accuracy for sleep stages S1 and REM [31]. In this work, a total number of 224 EEG recordings from eight subjects of two sleep stages such as S1 and REM were collected.…”
Section: A Datasetmentioning
confidence: 99%